DOI: 10.25148/etd.fidc004082
|View full text |Cite
|
Sign up to set email alerts
|

Drivers and Mechanisms of Peat Collapse in Coastal Wetlands

Abstract: It's been a long journey, and there are many people to thank who helped me get to this point. I would like to first and foremost thank my two wonderful advisors, Dr. Tiffany Troxler and Dr. Jennifer Richards, for taking a chance on me and allowing me the freedom to craft my research. Their constant guidance and feedback helped develop not only this dissertation but my character as well. I want to especially thank one member of my committee, Dr. John Kominoski. John took me into his lab from day one and has con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 86 publications
1
13
0
Order By: Relevance
“…Although we found little impact of GEP or ANPP with continuous exposure to elevated salinity, we found a decrease in live root biomass, although this effect was not significant when comparing the Salt + P to the Fresh treatment. This result supports other experiments in the Everglades that show that live root biomass in the soil significantly decreases with elevated salinity (Wilson ; Wilson et al., 2018 a , b). A decrease in live roots could result in less root binding of soil and less live root mass to replace senesced roots and overall compression of the soil matrix causing the soils to begun to slump and collapse (Delaune et al.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Although we found little impact of GEP or ANPP with continuous exposure to elevated salinity, we found a decrease in live root biomass, although this effect was not significant when comparing the Salt + P to the Fresh treatment. This result supports other experiments in the Everglades that show that live root biomass in the soil significantly decreases with elevated salinity (Wilson ; Wilson et al., 2018 a , b). A decrease in live roots could result in less root binding of soil and less live root mass to replace senesced roots and overall compression of the soil matrix causing the soils to begun to slump and collapse (Delaune et al.…”
Section: Discussionsupporting
confidence: 91%
“…). Another study conducted on the same mesocosm monoliths used in this study found that there was a ~2‐cm in elevation loss after only one year in the Salt + P compared to the Fresh treatment (Wilson ). Therefore, even though aboveground productivity and NEP increased with Salt + P, soil structure and integrity appeared to be negatively affected by salt and thus vulnerable to collapse.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations